Responsabilidad en las obligaciones derivadas de las actividades de intermediación laboral - Fabian Muncibay, José Antonio (2016)
It has prepared this work from the perspective of legal science with specific focus on labor law, whose star phenomenon is outsourcing in the form of labor mediation, addressing the dimensions of this new form of contract and the search for provide an overview of outsourcing from the legal perspective and highlighting its concept, benefits and risks as well as similarities and differences in intermediation and outsourcing processes in Peru with the various legislations. In it, general objetive determines whether the Peruvian law, after the effective date of the Law on Labor Intermediation N° 27626, guarantees the obligations of social security of the highlights to the user enterprise workers, as aforementioned protective response of our system effects such joint and several liability is concentrated, to the insecurity of workers from the contractor and principal. Finally some alternative care that tend to minimize the effects mentioned above arises, since under the legislative provisions of Law N° 27626 is precarious. In this context, what is sought is to enable mutual enrichment and improvement in standards from national and international experience.